Study of Health Education - Ahmed, Nadeem (Innovative Research Thoughts, 2017)
Since the 19th century, health education has been an established profession with a distinct set of 'knowledge, specified qualifications, experience and code of ethics.' It is a dynamic public-service sector which covers ideas and models from many disciplines such as education and training, health and medical studies, media & communication and anthropology. This exquisite academic mix shows its importance in society in the 21st century. As the name implies, health education focuses on and tackles the health problems of people and communities in general. It is founded on the concept of 'foresight prevention' To improve the efficacy of health education, it must be started as a social effort from the grassroots level. Social institutions such as schools, communities, families etc. appear to contribute to this. Health instruction at schools seems to have a multiplying and enduring impact on later-life pupils. In schools, it includes teaching and learning on and about knowledge, beliefs, attitudes, values, skills and skills in health. It focuses primarily on the health of school staff, especially children and generally on cleanliness, food and nutrition; hepatitis, cholera, dengue and polio, etc., endemic and epidemic transmissible illnesses